PEMUTlHAN KAYU DUN.JING (PARASERIANTHES FALCATARIA (L.) NIELSEN). DENGAN METODA RENDAM DAN LABUR - Sri Rulliaty (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
Tlae effect of chemical concentration and method of bleaching on the wood quality i8 reported in thia paper. The mmpla material co,..;.tetl of 40 piet:u jeur4/ing wood (Partueriantha (alcataria (L.) Nisllen.) meauri